THE EFFICIENCY OF SUGARCANE (Saccharum officinarum) FARMS USING THE DEA (DATA ENVELOPMENT ANALYSIS) APPROACH IN PURWOREJO REGENCY - Widyadhari Febriani Setyaningrum; Titik Ekowati; Budi Adi Kristanto (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2020)
The research was purposed to know the technical efficiency level of sugarcane farming in Purworejo regency. The research method used DEA (Data Envelopment Analysis) with the input-oriented assumption to measure the efficiency score from each observed farming. The result of the research showed most of the sugarcane farming in Purworejo regency was categorized as inefficient. According to DEA-CRS calculation, there were 11 sugarcane farming 19,3 %) who have operated efficiently and 46 sugarcane farming (80,7%) have not operated efficiently yet (inefficient). The efficiency calculation using Variable Return To Scale (VRS) assumption resulted in an average efficiency value of 0.937. Efficiency was reached by 21 people (36.84%) while the other 36 people (63.16%) still have not reached efficiency yet.